Targeting adenosine monophosphate-activated protein kinase (AMPK) in preclinical models reveals a potential mechanism for the treatment of neuropathic pain - Peebles Katherine A; Johnson Jessica; Khoutorsky Arkady; Lark Arianna; Yan Jin; Sanoja Raul; Tillu Dipti V; Asiedu Marina N; Melemedjian Ohannes K; Lepow Talya; Sonenberg Nahum; Dussor Gregory; et al. (Molecular Pain, 2011)
Abstract Neuropathic pain is a debilitating clinical condition with few efficacious treatments, warranting development of novel therapeutics. We hypothesized that dysregulated translation regulation pathways may underlie neuropathic pain. Peripheral nerve injury induced reorganization of translation machinery in the peripheral nervous system of rats and mice, including enhanced mTOR and ERK activity, increased phosphorylation of mTOR and ERK downstream targets, augmented eIF4F complex formation and enhanced nascent protein synthesis. The AMP activated protein kinase (AMPK) activators, metformin and A769662, inhibited translation regulation signaling pathways, eIF4F complex formation, nascent protein synthesis in injured nerves and sodium channel-dependent excitability of sensory neurons resulting in a resolution of neuropathic allodynia. Therefore, injury-induced dysregulation of translation control underlies pathology leading to neuropathic pain and reveals AMPK as a novel therapeutic target for the potential treatment of neuropathic pain.